Faculty Perceptions on Accessibility in Online Learning: Knowledge, Practice and Professional Development - Thelma C Guilbaud; Florence Martin; Xiaoxia Newton (Online Learning, 2021)
This study examined the level of readiness of faculty in designing and delivering accessible online courses to meet the needs of all learners, including students with disabilities. A total of 182 tenured/non-tenured full time, part-time, adjunct and clinical faculty from three public universities of different sizes were surveyed to gauge their awareness, understanding, and practices related to disability laws, quality standards, utilization of tools, and professional development support. Results from the study indicated an uneven level of readiness by faculty regarding online learning accessibility. Results from the study showed that professional development training in online learning had a very significant influence on accessibility knowledge and practice. Also, high perceptions of knowledge for institutional policy and terminology and low perception of accessibility laws and standards were found. It is also found that training on disability-related laws and regulations provided by higher education institutions was insufficient and at times, does not align with the faculty’s schedule. Given the results of the study, it is recommended that higher education institutions reorient their approach to supporting faculty who teach online and develop a comprehensive strategy to reach the goal of helping all students, including students with disabilities, to fully engage online learning. The findings from this study have implications for course development and implementation to support students with disabilities.